2009
DOI: 10.1038/sj.ejcn.1602976
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative effects on cardiovascular risk factors and coronary heart disease risk of replacing partially hydrogenated vegetable oils with other fats and oils

Abstract: Background/Objectives: Reduced consumption of trans-fatty acids (TFA) is desirable to lower coronary heart disease (CHD) risk. In practice, partially hydrogenated vegetable oils (PHVO) that contain both TFAs and other fatty acids are the unit of replacement and could be replaced with diverse alternative fats and oils. We performed quantitative estimates of CHD effects if a person's PHVO consumption were to be replaced with alternative fats and oils based on (1) randomized dietary trials and (2) prospective obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
244
1
16

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(276 citation statements)
references
References 45 publications
15
244
1
16
Order By: Relevance
“…Skeaff and Miller (2009) reported a highly significant association between CHD mortality and total CHD events and TFA intake in a meta-analysis of cohort studies. A similar result (based largely on the same cohort trials) was reported by Mozaffarian and Clarke (2009). This was also the outcome of an analysis based on causation score, taking into account four criteria: strength, consistency, temporality and coherence (Mente et al, 2009).…”
Section: Tfa and Cardiovascular Risksupporting
confidence: 71%
See 1 more Smart Citation
“…Skeaff and Miller (2009) reported a highly significant association between CHD mortality and total CHD events and TFA intake in a meta-analysis of cohort studies. A similar result (based largely on the same cohort trials) was reported by Mozaffarian and Clarke (2009). This was also the outcome of an analysis based on causation score, taking into account four criteria: strength, consistency, temporality and coherence (Mente et al, 2009).…”
Section: Tfa and Cardiovascular Risksupporting
confidence: 71%
“…This was also the outcome of an analysis based on causation score, taking into account four criteria: strength, consistency, temporality and coherence (Mente et al, 2009). Mozaffarian and Clarke (2009) also analyzed the results of a number of short-term intervention trials, which looked at the impact of replacing partially hydrogenated vegetable oil (PHVO), with a range of other dietary fats, on blood lipids and lipoproteins and other risk factors. They then used these data to estimate the possible impact of such substitutions on CHD risk.…”
Section: Tfa and Cardiovascular Riskmentioning
confidence: 99%
“…Moreover, the lack of beneficial effect of the L9 diet could also due to the huge increase in the trans-18:2 isomers. These isomers have been reported to be more deleterious than the trans-18:1 isomers (Baylin et al, 2003), for a review see Mozaffarian and Clarke (2009).…”
Section: Discussionmentioning
confidence: 99%
“…Comparado con AGMI o AGPI, los AGT aumentan los niveles TG plasmáticos en ayunas 45 y los niveles de Lp(a) 46 . Interesantemente otros factores dietarios (incluyendo otras grasas) al parecer no afectarían los niveles de Lp(a).…”
Section: Aumento De Triglicéridos Y Lp(a)unclassified